1993
DOI: 10.1109/58.212557
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the static performance of piezoelectric ceramic-polymer composites with 2-2 connectivity

Abstract: The static equilibrium conditions have been derived for piezoelectric-ceramic-polymer composite structures. Rigorous solutions are obtained for a 2-2 composite of lamellar configuration. Under a uniaxial stress or an electric field the strain profile becomes inhomogeneous due to different elastic stiffness of the two components (hard piezoelectric ceramics and soft polymer). The stress transfer between the two components is identified as due to an additional shear stress produced at the ceramic-polymer interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…We attribute such differences to the effects of nonuniform surface deflections. In related work, Cao and co-workers 30,31,43 have shown that the actual displacement profile is nonuniform for 2-2 and 1-3 composites, which leads to a stress concentration in the PZT pillars that is significantly less than predicted under the isostrain assumption. This effect was exacerbated for thin composites, such as those studied here.…”
Section: B Properties Of Pzt Monoliths and 3-x Pzt-polymer Compositesmentioning
confidence: 95%
See 1 more Smart Citation
“…We attribute such differences to the effects of nonuniform surface deflections. In related work, Cao and co-workers 30,31,43 have shown that the actual displacement profile is nonuniform for 2-2 and 1-3 composites, which leads to a stress concentration in the PZT pillars that is significantly less than predicted under the isostrain assumption. This effect was exacerbated for thin composites, such as those studied here.…”
Section: B Properties Of Pzt Monoliths and 3-x Pzt-polymer Compositesmentioning
confidence: 95%
“…The dielectric constant (K 3 ), piezoelectric constants (d 33 and d 31 ), and electromechanical coupling coefficients (k P and k 31 ) determined for monolithic PZT disks are reported in Table IV. The properties of both robocast ͑RC͒ and cold isostatically pressed ͑CIP͒ disks exhibited good agreement with the reported properties for bulk PZT, 47 with variations of less than ϳ7% observed.…”
Section: B Properties Of Pzt Monoliths and 3-x Pzt-polymer Compositesmentioning
confidence: 99%
“…It is known based on the connective characteristic of two-phase composite [6], piezoelectric composites can usually be divided into ten basic connectivity patterns. The 2-2 connectivity piezoelectric composites have received extensive attention due to the simple fabrication technique and superior sensing and actuating abilities, and many studies have also been reported referring to the fabricating technique, property and theoretical investigation of 2-2 connectivity piezoelectric composite [7][8][9][10][11]. In 2002, Zhang et al [12,13] fabricated 2-2 connectivity cement based piezoelectric composites by casting cement-based mortar into a series of pre-arranged piezoelectric thin plates and investigated the sensing and actuating effects of this composite.…”
Section: Introductionmentioning
confidence: 99%
“…Being a biphasic material, the properties of a piezocomposite can be tailored over a wide range by adjusting the material properties and geometric shape of constituting phases. This provides significant technological advantages for the transducer design [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%